Examining the Effects of Physical Environment and Structural Characteristics on the Spatial Patterns of Crime in Daegu, South Korea - Kim, Young-An (Crime & delinquency, 2024)
The current study examines the relationship between the features of physical and social environments and neighborhood crime in a large Korean city. We utilized the 112 Crime Calls Data from May 1, 2018 to April 30, 2019, aggregated at the ¼-mile egohood level. We estimated a series of negative binomial regression models to test the effects of social and physical environmental features on crime rates. Furthermore, we examine potential moderating effects between the measures of physical and social environments. The results indicate that incorporating the physical and social environmental features based on the theoretical framework of criminal opportunities and social disorganization can be useful for understanding the spatial patterns of crime in Korean context.